Самоэффективность и саморегуляция как важные психологические факторы активной профессиональной позиции управленческого персонала вузов - Смирнова, Л.Н.; Ищанова, Р.С. (My University, 2016)
The relevance of the study determined a significant increase in the qualitative and quantitative changes in the socio-economic life of society, and hence the objective of modern requirements for professional activity at all levels, one of which - their active professional position. On the basis of comparing the diagnostic results of the two groups - the representatives of the administrative staff of universities assessed the range of ties active professional position Ithaca psychological variables such as self-efficacy and self-regulation.
Keywords: active professional position; self-efficacy; self-regulation